Kinetic and Thermodynamics of Methylene Blue Adsorption onto Zero Valent Iron Supported on Mesoporous Silica - Atyaf Khalid Hameed; Nugroho Dewayanto; Du Dongyun; Mohd Ridzuan Nordin; Mohd Hasbi Ab Rahim (Bulletin of Chemical Reaction Engineering & Catalysis, 2016)
Zero valent iron supported on mesoporous silicanano particles (NZVI/MSNs) was prepared by the aqueous phase borohydride reduction methods. Prior to the reduction, mesoporous silica nanoparticles (MSNs) were prepared through the activation of fumed silica with concentrated HCl by refluxing at 90 °C. FTIR, XRD, FESEM, EDX and BET were used to characterize theadsorbents prepared. BET surface areas of MSNs, NZVI, and NZVI/MSNs were 126, 41, and 72 m2/g for, respectively. The performance of NZVI/MSNs as adsorbent was examined by adsorption of methylene blue (MB), performed in series of batch experiments. In the kinetic studies, pseudo first order and pseudo second order kinetic models were examined. The pseudo second order equation provided the best fit with the experimental data. Thermodynamic studies indicated that the adsorption process is endothermic with ΔH° was 90.53 kJ/mol. Positive ΔS° (300 J/mol) and negative ΔG° (-6.42 kJ/mol) was recorded, indicating the spontaneous of the adsorption process and naturally favorable.